Frequency of consumption of balanced meals, bodyweight gain and incident risk of glucose intolerance in Japanese men and women: A cohort study. Issue 5 (22nd September 2020) - Sakurai, Masaru; Ishizaki, Masao; Morikawa, Yuko; Kido, Teruhiko; Naruse, Yuchi; Nakashima, Yuki; Okamoto, Chiaki; Nogawa, Kazuhiro; Watanabe, Yuuka; Suwazono, Yasushi; Hozawa, Atsushi; Yoshita, Katsushi; et al.
Abstract: Aims/Introduction: This cohort study assessed the risk for bodyweight gain and development of glucose intolerance based on the frequency of consumption of balanced meals including grain, fish or meat and vegetables. Materials and Methods: The participants (8, 573 men, 3, 327 women) were employees of a company in Japan. A self‐administered questionnaire was used to evaluate the frequency of balanced meal consumption. Bodyweight changes and the incidence of glucose intolerance (glycated hemoglobin >6.0%) during the 3‐year follow‐up period were determined through annual health examinations. Results: The mean bodyweight change over a period of 3 years was 0.78 kg for men and 0.84 kg for women. A lower frequency of balanced meals was associated with a higher bodyweight gain for men ( P for trend = 0.004), but not for women. During the study, 464 men and 115 women developed glucose intolerance. Overall, the frequency of balanced meals was not associated with the risk of glucose intolerance in either sex. However, the interaction between the frequency of balanced meals and degree of obesity had a significant effect on the incidence of glucose intolerance in men ( P = 0.005), with less frequent consumption of balanced meals being associated with a higher risk for glucose intolerance among men with a BMI ≥25.0 kg/m 2 ( P for trend = 0.007). Conclusions: A higher frequency of balanced meals, including grain, fish or meat and vegetable dishes – important components of healthy Japanese food – was associated with a lower risk of glucose intolerance in obese men, but not in non‐obese men and women. Abstract : We evaluated the risk for development of glucose intolerance based on the frequency of consumption of balanced meals including grain, fish and meat, and vegetable dishes. A lower frequency of balanced meals was associated with a higher risk of glucose intolerance in obese men.